Robert Browning's language - Hair, Donald S. (University of Toronto Press, 1999)
"What are the influences that shaped the language used by one of the nineteenth century's greatest writers? How did his religious beliefs, the books he owned, the paintings and music he loved, affect almost sixty years' output of poems, plays, essays, and letters?" "This book attempts to define Browning's understanding of the nature and use of words and syntax by considering not only a full range of texts from the 1833 Pauline to the 1889 Asolando, but also the ideas important to Browning, the historical context in which he lived, and the other artistic passions that played a part in his life."--Jacket